Potential Natural Antibacterial Agent for P. gingivalis Periodontitis Infection: A Comprehensive Review of Source, Structure and Mechanism actions - Amin, Meiny Faudah; Ariwibowo, Taufiq; Putri, Salsabila Aqila; Kurnia, Dikdik (Faculty of Dentistry, Universitas Islam Sultan Agung, 2024)
The pathogenic bacteria P. gingivalis grows in the oral cavity. This bacterium could attack immune system which lead to inflammation of most tissues. P. gingivalis can cause a variety of serious and dangerous condition such as periodontitis, Alzheimer, rheumatoid arthritis, diabetes, and pneumonia. Antibiotics have been used for years as a treatment against this bacterium, like metronidazole, amoxicillin, and clindamycin, however, P. gingivalis is reported to be resistant to these antibiotics, thus exploration to discover alternatives has been demanded. Natural product compounds are known to have antibacterial activity and cause fewer side effects. Turmeric, eucalyptus, and several other plants have been reported to have antibacterial activity against P. gingivalis with a MIC of 1g/mL from an ethyl acetate leaf extract of eucalyptus. Decent antibacterial activity could be used as a reference to discover new drugs as alternatives against P. gingivalis